A lightweight traceability assessment method for medical device software. Issue 4 (6th October 2011) - Casey, Valentine; Mc Caffery, Fergal; Biró, Miklós; Messnarz, Richard; Palacios, Ricardo Colomo
SUMMARY Traceability is central to medical device software development and essential for regulatory approval. For compliance to be achieved, an effective traceability process needs to be in place. This process must ensure the need for clear linkages and traceability from software requirements – including risks – through the different stages of the software development and maintenance lifecycles. This is difficult to achieve because of the lack of specific guidance within the medical device standards and documentation. This has resulted in many medical device companies employing inefficient software traceability processes. In this paper, we outline the development and implementation of Med‐Trace, a lightweight software traceability process assessment and improvement method developed specifically for the medical device industry. We also present and discuss findings from two industry‐based Med‐Trace assessments. Copyright © 2011 John Wiley & Sons, Ltd.